The Myth of Charismatic Leaders - Joseph A. Raelin (T+D - Training and development, 2003)
Why do we idolize our leaders? Maybe it is because our culture still admires individualism, or maybe because we fear what is to come. But either way, says Raelin, we must develop a shared management style in order to brave the future. Following someone strictly for inspirational vision can be a waste of time and even dangerous, particularly when collaboration can yield better results. Charismatic leaders are often not as good in some situations as they are hoped or expected to be. In fact, many tend to be narcissistic, egocentric, or hard-driving. Followers often choose such "hero leaders" for psychological comfort during times of distress, rather than their ability to manage conflict. They see this person as a savior and the only person able to lead them through the trouble. The problem is, Raelin argues, that we often overemphasize a leader's powers and expect one person to make all of the decisions, rarely considering anyone else's contributions. What's more effective is a collaborative leadership, in which anyone can assume power when needed. That way, resolutions are based on merit rather than on blind faith.
Keywords: I20; J24; L20; M10; M12; M14; M50; M53; O15; O31; 330; Charisma; Charismatic leadership; Collaboration; Collaborative leadership; Romanticism; Heroes